The community of the college of justice Edinburgh and the Court of Session, 1687-1808 - Finlay, John. (Edinburgh : Edinburgh University Press, 2012)
How important can a court and its members be in influencing the development of a country? In Scotland's case, the answer is surprising. This book shows the development of Edinburgh's history as an example of community interaction in an urban setting in comparison to courts across Europe and elsewhere.
Specialized.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Scotland. -- Court of Session -- History; Civil procedure -- Scotland -- History; Edinburgh (Scotland) -- Intellectual life -- 17th century; Edinburgh (Scotland) -- Intellectual life -- 18th century; Edinburgh (Scotland) -- Intellectual life -- 19th century; Law